Effectiveness of a foot self-management intervention that utilized commercially available infrared thermometers: Mixed methods research incorporating a pilot RCT. Issue 1 (February 2023) - Stevens, Kathleen; Moralejo, Donna; Ersser, Steven; MacLean, Cathy
Abstract: Objective: To evaluate the effectiveness of a foot self-management strategy that utilized a commercially-available infrared thermometer (CAIT) for prevention of diabetic foot ulcers. Research Design and Methods: In this six-month pilot randomized controlled trial, Phase 2 of a three-phase mixed methods research study, 62 participants were randomized to a thermometer and education group (n = 34) and an education-only group (n = 26). Both groups received foot care education and were assessed by a certified orthotist. All participants recorded their number of steps and recorded a foot assessment in a logbook daily. The thermometer and education group also recorded their daily temperature assessment. A temperature difference of >4° Fahrenheit (F) between the two feet prompted participants to rest their feet. Participants were directed to see their healthcare provider if the temperature difference did not decrease to below 4° F in two days. Phase 3 of the study explored the Phase 2 results to understand the findings further. Results: The strategy improved foot assessment and action: the thermometer and education group had significantly more days with any assessment completed than the education-only group (150.98/180 vs. 119.84/180, p = 0.02). Phase 3 findings showed that the thermometer engaged participants, prompted action, and offered reassurance regarding foot health. Conclusions: A CAIT is a tool that could support foot self-management and may offer several benefits, such as promoting and providing structure for a foot assessment and direction for action. Clinical trial reg no: NCT0306776 clinicaltrials.gov . Highlights: Monitoring of foot temperature with a medical-grade thermometer is a strategy to help patients identify inflammation that could lead to an ulcer. We wanted to ask whether daily temperature monitoring with a low-cost commercially available infrared thermometer supports self-management. We found that the strategy engaged patients, improved foot assessment, and prompted action to address foot concerns. The low-cost commercially available thermometer is a tool that could support foot self-management and prevent foot ulcers.